Four new species of polychromatic spiny-tailed iguanian lizards, genus Stenocercus (Iguania: Tropiduridae), from Peru - Venegas, Pablo J.; García-Ayachi, Luis A.; Chávez-Arribasplata, Juan C.; García-Bravo, Antonio (Zootaxa, 2022)
The tropical Andes Mountains exhibit high levels of endemism and spatial turnover in the distribution of species. The lizard genus Stenocercus Duméril & Bibron, 1837, contains 76 species and most of them occur in the tropical Andes, reaching elevations up to 4,000 m. We describe four new species of Stenocercus based on the examination of newly collected material from the Amazonian slopes of the Peruvian Andes. Stenocercus asenlignus sp. nov. inhabits the premontane forest of northern and central Peru, departments of Amazonas, San Martín and Huánuco, at elevations between 1,500 and 2,036 m, in the basins of the Mayo, Huayabamba, and Huallaga rivers. Stenocercus leybachi sp. nov. inhabits the premontane forest of the upper Huallaga River, Huánuco department in central Peru, at elevations between 824 and 1,270 m. Stenocercus qalaywasi sp. nov. was collected in a small village at the headwaters of the Mantaro River, Junín department in central Peru, at an elevation of 2,587 m. Finally, S. nigrocaudatus sp. nov. inhabits the montane forest from extreme northern Peru, Cajamarca department, at elevations of 1,700 and 1,892 m. These species are characterized by having granular scales on the posterior surface of the thighs, relatively short tail, caudals spinose, two caudal whorls per autotomic segment, and the ability to change coloration from green to brown or gray; they differ from other species of Stenocercus in scutellation features and color pattern.